Lumican silencing alleviates tumor necrosis factor-α-induced nucleus pulposus cell inflammation and senescence by inhibiting apoptosis signal regulating kinase 1/p38 signaling pathway via inactivating Fas ligand expression. Issue 1 (1st January 2021) - Li, Zhenqiang; Sun, Chengfeng; Chen, Maosong; Wang, Boding
ABSTRACT: A recent study has reported that lumican (LUM) is expressed at a high level in the nucleus pulposus specimens from herniated lumbar disc, without description of the specific mechanism. This study was designed to investigate the function and mechanism of LUM in intervertebral disc degeneration (IDD). In this study, human nucleus pulposus cells (hNPCs) cells were challenged with tumor necrosis factor (TNF)-α to establish the IDD in vitro model. After LUM silencing, cell viability was detected using CCK-8 kit, and the expression of inflammatory factors was evaluated using RT-qPCR and ELISA. Flow cytometry and β-galactosidase staining were used to determine cell cycle and cell senescence. The expression of cycle and senescence-related proteins was evaluated with western blotting. Then, Fas ligand (FasL) was overexpressed and proteins in apoptosis signal regulating kinase 1 (ASK1)/p38 signaling were tested. Finally, GS-4997, an inhibitor of ASK1, was used to explore the regulatory effects of LUM on ASK1/p38 signaling in TNF-α-induced hNPCs. Results indicated that LUM expression was upregulated in TNF-α-challenged hNPCs. LUM gene interference mitigated TNF-α-induced inflammatory response, cell cycle arrest, and senescence of hNPCs. It was then found that LUM silencing could inhibit ASK1/p38 signaling in TNF-α-treated hNPCs, which was reversed by FasL overexpression. Additionally, ASK1/p38 participated in the mediation by LUM of TNF-α-induced inflammation, cell cycle arrest, and senescence of hNPCs. To conclude, interference with LUM effectively mitigated TNF-α-induced inflammatory response, cell cycle arrest, and cell senescence. Further experiments showed the involvement of ASK1/p38 pathway in LUM-mediated NP cell phenotypes through FasL.